Financialization, possessive familialism, and the politics of vacancy: How vacancy became Greece’s most lucrative housing strategy - Nikos Vrantsis (Radical Housing Journal)
This paper reinterprets urban vacancy in Greece not as market failure, but as a calculated tool for profit. Focusing on Thessaloniki, it argues that vacancy is produced, maintained, repurposed, and removed by financial actors to maximize returns. These actors withhold properties from circulation, controlling the timing of their reintegration into the market to sustain speculation and property inflation. This process is reinforced by state policies, landlord lobbying, and Greece’s entrenched system of possessive familialism, which has shaped private property ideologies that normalize property hoarding. The findings emerge from qualitative research including interviews with financial actors, displaced tenants, and foreclosed homeowners. The study examines the power structures that regulate access to housing. It categorizes vacant properties by ownership profile and investment logic, exposing how landlords, financiers, and the state engineer scarcity to drive up property values. By situating vacancy within the broader restructuring of Greece’s property regime, this paper challenges mainstream supply-demand narratives and reveals vacancy as a mechanism of rent extraction and urban exclusion.